Numerical Simulation of Rock Fragmentation under the Impact Load of Water Jet - Jiang Hongxiang; Du Changlong; Liu Songyong; Gao Kuidong (Shock and Vibration)
To investigate the rock fragmentation and its influence factors under the impact load of water jet, a numerical method which coupled finite element method (FEM) with smoothed particle hydrodynamics (SPH) was adopted to simulate the rock fragmentation process by water jet. Linear and shock equations of state were applied to describe the dynamic characteristics of rock and water, respectively, while the maximum principal stress criterion was used for the rock failure detection. The dynamic stresses at the selected element containing points in rock are computed as a function of time under the impact load of water jet. The influences of the factors of boundary condition, impact velocity, confining pressure, and structure plane on rock dynamic fragmentation are discussed.